PENGEMBANGAN E-LKPD BERBASIS PROBLEM BASED LEARNING PADA PEMBELAJARAN GEOGRAFI MATERI LINGKUNGAN SEBAGAI HABITAT HIDUP BERKELANJUTAN TERHADAP HASIL BELAJAR SISWA KELAS XI SMA NEGERI 1 DRIYOREJO - Shierlyra Fedrani A’ineviska; Sukma Perdana Prasetya; Ita Mardiani Zain; Sri Murtini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low learning outcomes of students in geography subjects at SMA Negeri 1 Driyorejo. The results of the daily tests of grade XI students in 2024 showed that 62.9% of students obtained scores below the Learning Objectives Achievement Criteria (KKTP) of 80. This condition indicates the need for innovative teaching materials that can improve student learning outcomes. This study aims to determine the feasibility and effectiveness of using E-LKPD based on Problem Based Learning (PBL) on environmental material as a sustainable living habitat. The research method used is Research and Development (R&D) with the ADDIE model which includes the stages of Analyze, Design, Development, Implementation, and Evaluation. The research subjects were grade XI-11 students. Data sources were obtained from the validation results of expert lecturers and geography subject teachers as well as the results of student Pre-Tests and Post-Tests. The research instruments were validation sheets and student learning outcome tests. Data analysis techniques included validity, reliability, normality tests, Paired Sample T-Tests and N-Gain tests. The results of the study indicate that PBL-based E-LKPD is very feasible to use with a percentage of 93.3% assessment from expert lecturers and 96.6% from geography subject teachers. The average student score increased from 51.25 in the Pre-Test to 82.22 in the Post-Test with a difference of 30.97. The N-Gain value of 0.64 is included in the moderate category with an effectiveness interpretation of 64.39% including the fairly effective category. The Paired Sample T-Test test shows a significance value of 0.000 <0.05 so that there is a significant difference between the Pre-Test and Post-Test scores, thus PBL-based E-LKPD improves student learning outcomes in geography learning.